Dialect change in resident killer whales: implications for vocal learning and cultural transmission - Deecke, V B; Ford, J K B; Spong, P (Animal Behaviour, 2000)
Variation in vocal signals among populations and social groups of animals provides opportunities for the study of the mechanisms of behavioural change and their importance in generating and maintaining behavioural variation. We analysed two call types made by two matrilineal social groups of resident killer whales, Orcinus orca, over 12-13 years. We used a neural network-based index of acoustic similarity to identify mechanisms of call differentiation. A test for structural modification of the calls detected significant changes in one call type in both groups, but not in the other. For the modified call type, the rate of divergence between the two groups was significantly lower than the rate of modification within either group showing that calls were modified in a similar fashion in the two groups. An analysis of structural parameters detected no strong directionality in the change. The pattern of call modification could have been caused by maturational changes to the calls or, if killer whale dialects are learned behavioural traits, cultural drift in the structure of the calls together with horizontal transmission of modifications between the two groups. Such vocal matching between members of different matrilines would suggest that vocal learning is not limited to vertical transmission from mother to offspring, which has important implications for models of gene-culture coevolution. (C) 2000 The Association for the Study of Animal Behaviour.